Psychospołeczne predyktory zachowań ryzykownych młodzieży = Psychosocial predictors of risk behaviours of children and adolescents - Grzegorzewska, Iwona (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Risk behaviours are an indispensable part of mental "growing up" of a human. Between the age of 10 and 20, a very particular process related to the formation of individual identity takes place. As a result of mental changes happening at the time, young people possess a strong desire to determine their own "I" what is usually done by less or more acute confrontation with the world of adults.
Keywords: zachowania ryzykowne; dorastanie; eksternalizacja problemów; czynniki ryzyka; problem behaviours; adolescence; externalization of problems; risk factors